Theta band transcranial alternating current stimulations modulates network behavior of dorsal anterior cingulate cortex - Keiichi Onoda (Nature Portfolio, 2017)
Abstract Dorsal anterior cingulate cortex (dACC) is an important region in the processing of both cognition and affect. Recently, transcranial brain stimulation has been used to modulate cortical activity, but it is unclear whether this stimulation has a specific effect on dACC. Based on EEG evidence that frontal midline theta activity is generated in dACC, we hypothesized that transcranial alternating current stimulation (tACS) with theta band frequency would modulate neural networks including dACC. In this study, we examined the effects of theta band tACS on functional networks and emotional state. Graph theory analysis for resting-state functional MRI data revealed that theta band tACS decreased functional integration and hub capacity in dACC, and the attenuation of dACC network function was associated with emotional state change. Overall, these results demonstrate that theta band stimulation can modulate dACC.